Transcriptome Analysis of the Response of Mature Helicobacter pylori Biofilm to Different Doses of Lactobacillus salivarius LN12 with Amoxicillin and Clarithromycin - Fang Jin; Hong Yang (MDPI AG, 2022)
Helicobacter pylori is a gastrointestinal pathogen with a high infection rate. Probiotics are clinically used as an adjuvant to improve the cure rate and reduce the side effects of antibiotic treatment for H. pylori. This study is the first to explore the effects of a cell-free supernatant of high- or low-dose Lactobacillus salivarius LN12 combined with amoxicillin (AMX) and clarithromycin (CLR) on H. pylori 3192 biofilms in terms of the biofilm biomass, survival rates, biofilm structure, and transcriptome. The results showed that the combination of the CFS of high-dose LN12 with AMX and CLR had stronger effects on the biofilm biomass, survival rate, and structure of H. pylori 3192 biofilms. H. pylori 3192 biofilms may increase the expression of NADH-related genes and downregulate flagellar assembly and quorum sensing-related receptor genes to deal with the stronger stress effects of high-dose LN12 with AMX and CLR. In conclusion, the biofilm biomass, survival rate, structure, and transcriptome results showed that the combination of LN12 CFS with AMX and CLR had dose effects. We recommend that compared with low doses, high doses of L. salivarus LN12 combined with AMX and CLR may be more effective for H. pylori biofilm than low doses.